CRISPR-Based Activation of Endogenous Expression of TPM1 Inhibits Inflammatory Response of Primary Human Coronary Artery Endothelial and Smooth Muscle Cells Induced by Recombinant Human Tumor Necrosis Factor α - Gagat, Maciej; Zielińska, Wioletta; Mikołajczyk, Klaudia; Zabrzyński, Jan; Krajewski, Adrian; Klimaszewska-Wiśniewska, Anna; Grzanka, Dariusz; Grzanka, Alina (Frontiers in Cell and Developmental Biology, 2021)
Tumor necrosis factor α (TNFα) is one of the most important proinflammatory cytokines, which affects many processes associated with the growth and characteristics of endothelial, smooth muscle, and immune system cells. However, there is no correlation between most in vivo and in vitro studies on its role in endothelial cell proliferation and migration. In this study we examined the effect of recombinant human (rh) TNFα produced in HEK293 cells on primary human coronary artery endothelial cells (pHCAECs) in the context of F-actin organization and such processes as migration and adhesion. Furthermore, we evaluated the possibility of the inhibition of the endothelial inflammatory response by the CRISPR-based regulation of tropomyosin-1 (TPM1) gene expression. We showed that TNFα-induced activation of pHCAECs was related to the reorganization of the actin cytoskeleton into parallelly-arranged stress fibers running along the longer axis of pHCAECs. It allowed the cells for directed and parallel motion during coordinated migration. This change in F-actin organization promoted strong, but discontinuous cell-cell contacts involved in signalization between migrating cells. Moreover, this form of intercellular connections together with locally increased adhesion was related to the formation of migrasomes and further migracytosis. Stabilization of the actin cytoskeleton through the CRISPR-based activation of endogenous expression of TPM1 resulted in the inhibition of the inflammatory response of pHCAECs following treatment with rh TNFα and stabilization of cell-cell junctions through reduced cleavage of VE-cadherin and maintaining the stable levels of α- and β-catenins. We also showed that CRISPR-based activation of TPM1 expression reduced inflammatory activation, proliferation and migration of primary human coronary artery smooth muscle cells. Therefore, TPM1 may be a potential therapeutic target for the treatment of proinflammatory vascular disorders.